New Fixed Point Results via \(C\)-class Functions in \(b\)-Rectangular Metric Spaces - Ansari, Arslan Hojat; Aydi, Hassen; Kumari, P. Sumati; Yildirim, Isa (Communications in Mathematics and Applications, 2018)
In this paper, we prove some xed point results in the setting of b-rectangular metric space via \(C\)-class functions. Moreover, in the last part of the paper, we point out that there is a slight aw in the proof of Erhan et al. [4, Theorem 4] and present a correct version of the theorem.